Resting-state brain network in Parkinson’s disease with different degrees of depression - Liu, Qinru; Mao, Zhenni; Tan, Changlian; Cai, Sainan; Shen, Qin; Wang, Min; Li, Junli; Zhang, Lin; Zhou, Fan; Song, Chendie; Yuan, Jiaying; Liu, Yujing; et al. (Frontiers in Neuroscience, 2022)
Objective: To explore the neural network mechanism of Parkinson's disease (PD) with different degrees of depression using independent component analysis (ICA) of the functional connectivity changes in the forehead, limbic system, and basal ganglia regions. Methods: 106 PD patients were divided into three groups: PD with moderate-severe depression (PDMSD, n=42), PD with mild depression (PDMD, n=29), and PD without depression (PDND, n=35). Fifty gender- and age-matched health objects were recruited as a control group (HC). Three-dimensional T1-weighted image and resting-state functional magnetic resonance imaging (RS-fMRI) data were collected. Results: Different functional connectivity was observed in the left precentral gyrus, right precuneus, right inferior frontal gyrus, right medial and paracingulate gyrus, left supplementary motor area, right brain insula, and the inferior frontal gyrus of the left orbit among 4 groups (ANOVA, P<0.05, Voxel size>5). Both PDMD and PDMSD exhibited an increased functional connectivity in the superior-posterior default-mode network (spDMN) and left frontoparietal network (LFPN); they also exhibited a decreased functional connectivity in the interior Salience Network (inSN) when compared with the PDND group. The functional connectivity within the inSN network was decreased in the PDMSD group when compared with the PDMD group (Alphasim correction, P<0.05, voxel zise>5). Conclusion: PD with different degrees of depression has abnormal functional connectivity in multiple networks, which is an important neurobiological basis for the occurrence and development of depression in PD. The degree of decreased functional connectivity in the inSN network is related to the degree of depression in PD-D patients, which can be an imaging marker for PD to judge the severity of depression.